PERAN PEMERINTAH DAERAH MELALUI DINAS PERTANIAN DALAM RANGKA MENINGKATKAN HASIL PRODUKSI PETANI - Yuni Hartono; Arumatul Islamiyah (JOURNAL AKSES STIA MALANG, 2021)
The role of the Regional Government through the Department of Agriculture in order to increase the production of citrus farmers can be seen from training, counseling on easy access to knowledge, technology and information on strengthening farmer institutions, especially in farmer groups in the Weru Asih Farmer Group, Tegalweru Village. Researchers want to know whether in general it is quite in accordance with the roles of the Regional Government referred to by the Dau District Agriculture Service, in carrying out its role and meeting the needs of citrus farmers, so that citrus farmers in this Farmers Group can be even better in Government referred to by the Dau District Agriculture Service, in carrying out its role and meeting the needs of citrus farmers, so that citrus farmers in this Farmers Group can be even better in their performance so that they are able to produce total citrus production. which continues to increase. The purpose of this study was to describe the role of the local government through the Department of Agriculture in Dau District in an effort to increase citrus production in Tegalweru Village, Dau District, Malang Regency, and how the yield of citrus agricultural production in Tegalweru Village, Dau District, Malang Regency. This research, was conducted by using a qualitative research approach with a descriptive type of research that aims to describe the data in the research field. The technique used in the form of observation, interviews and documentation. The data analysis used is a qualitative descriptive analysis technique that is carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study are how the role of the Regional Government through the Agriculture Service of Dau District in an effort to increase the production of citrus in Tegalweru Village, Dau District, Malang Regency, is to provide counseling / guidance related to citrus farming, then also provide facilities in the form of vehicles / transportation, namely Tossa, and tools for cultivating soil on citrus farms, then the results of citrus agricultural production in Tegalweru Village, Dau District, Malang Regency, namely there is a significant increase, which is about 50% of the comparison in 2019 and 2020. Keywords : Role, Local Government, Departement of Agliculture, Orange Production.